Basic perioperative transesophageal echocardiography : a multimedia review - Savage, Robert M., 1950-; Aronson, Solomon. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins Health)
"The editors of the Comprehensive Textbook of Perioperative Transesophageal Echocardiography have created a new product entitled Basic Perioperative Echocardiography and Review. Consisting of a short, full-color paperback book with a bound-in DVD, this product was developed with the recent endorsement of the ASA of an extensive educational program to train its members as well as creating a certification process with the NBE for its members in basic echocardiography. The book covers the basics--how to set up the machine, how to acquire the different views, relevant cardiac anatomy and pathophysiology, normal and abnormal values, how to perform the TEE exam, as well as basic assessment and interpretation skills. Each chapter ends with questions and answers. The DVD consists of 3D animations of the probe scanning the heart correlated to TEE video output, as well as rotating 3D animations of cardiac anatomy, enabling the user to see what is being scanned (anatomy), the position of the scanner, and the appearance of anatomy and pathophysiology via the TEE video output at once. The intended audience is anyone interested in basic TEE skills: anesthesiologists, cardiologists, as well as critical care practitioners"--Provided by publisher.